Evaluation of open pollinated and hybrid maize varieties in Dhading district of Nepal - Devkota, Shivahari; Karn, Rupak; Jha, Ritesh Kumar; Marasini, Dinesh; Sah, Shrawan Kumar (Journal of Agriculture and Natural Resources, 2020)
Five maize varieties namely Rampur composite, Arun-2, Manakamana-3, Rampur Hybrid-4 and Rajkumar were evaluated in randomized complete block design with four replications at farmers field at Nilkantha Municipality-09, Aashikhola, Dhading from February 2018 to June 2018 to identify high yielding maze  varieties. Significant variation  was observed for grain yield, silking and tasseling, number of kernels per cob and cob length.The largest cob length was found in Rampur composite (19.550 cm) and highest number of kernel row per cob  was found in Rajkumar (17.25) and Manakamana-3 (17.25).The highest number of leaves above cob  was found in Rampur composite (5.678). The number of days for 50% tasseling and number of days for 50% silking had a highly significant and positive correlation with plot yield. The highest number of days for 50% tasseling (78.50 DAS) and days for 50 % silking (82.50 DAS) was observed in the genotypes Rampur Hybrid-4. Similarly, the number of leaves above the cob , thousand kernel weight and length of the cob  had a significant and positive correlation with plot yield. Rampur Hybrid -4 was the highest yielding genotype (7.79 t/ha) for such domain area with a B:C ratio of 1.48.Thus, Rampur Hybrid-4 genotype is recommended for spring season in Dhading.